Long-term mortality outcome of a primary care-based mobile health intervention for stroke management: Six-year follow-up of a cluster-randomized controlled trial. - Xingxing Chen; Enying Gong; Jie Tan; Elizabeth L Turner; John A Gallis; Shifeng Sun; Siran Luo; Fei Wu; Bolu Yang; Yutong Long; Yilong Wang; Zixiao Li; et al. (PLoS Medicine)
Background Despite growing evidence of primary care-based interventions for chronic disease management in resource-limited settings, long-term post-trial effects remain inconclusive. We investigated the association of a 12-month system-integrated technology-enabled model of care (SINEMA) intervention with mortality outcomes among patients experiencing stroke at 6-year post-trial. Methods and findings This study (clinicltiral.gov registration number: NCT05792618) is a long-term passive observational follow-up of participants and their spouse of the SINEMA trial (clinicaltrial.gov registration number: NCT03185858). The original SINEMA trial was a cluster-randomized controlled trial conducted in 50 villages (clusters) in rural China among patients experiencing stroke during July 2017-July 2018. Village doctors in the intervention arm received training, incentives, and a customized mobile health application supporting monthly follow-ups to participants who also received daily free automated voice-messages. Vital status and causes of death were ascertained using local death registry, standardized village doctor records, and verbal autopsy. The post-trial observational follow-up spanned from 13- to 70-months post-baseline (up to April 30, 2023), during which no intervention was requested or supported. The primary outcome of this study was all-cause mortality, with cardiovascular and stroke cause-specific mortality also reported. Cox proportional hazards models with cluster-robust standard errors were used to compute hazard ratios (HRs) and 95% confidence intervals (95% CIs), adjusting for town, age, and sex in the main analysis model. Analyses were conducted on an intention-to-treat basis. Of 1,299 patients experiencing stroke (mean age 65.7 years, 42.6% females) followed-up to 6 years, 276 (21.2%) died (median time-to-death 43.0 months [quantile 1-quantile 3: 26.7-56.8]). Cumulative incidence of all-cause mortality was 19.0% (121 among 637) in the intervention arm versus 23.4% (155 among 662) in the control arm (HR 0.73; 95% CI 0.59, 0.90; p = 0.004); 14.4% versus 17.7% (HR 0.73; 95% CI 0.58, 0.94; p = 0.013) for cardiovascular cause-specific mortality; and 6.0% versus 7.9% (HR 0.71; 95% CI 0.44, 1.15; p = 0.16) for stroke cause-specific mortality. Although multisource verification was used to verify the outcomes, limitations exist as the survey- and record-matching-based nature of the study, unavailability of accurate clinical diagnostic records for some cases and the potential confounders that may influence the observed association on mortality. Conclusions Despite no observed statistically difference on stroke cause-specific mortality, the 12-month SINEMA intervention, compared with usual care, significantly associated with reduced all-cause and cardiovascular cause-specific mortality during 6 years of follow-up, suggesting potential sustained long-term benefits to patients experiencing stroke.